2008
DOI: 10.1007/s11239-008-0266-2
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in local hemostasis activation following percutaneous coronary intervention in stable angina patients: a comparison between drug-eluting and bare metal stents

Abstract: Early changes in local hemostasis activation following PCI, were related to balloon predilation. Neither DES nor BMS increased markers of platelet activation, coagulation, or fibrinolysis, under dual antiplatelet and anticoagulant pretreatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…In particular, the more aggressive the procedures (i.e. with RA), the more pronounced this biomarker reduction, suggesting that endothelial dysfunction potentially occurs post‐PCI, in line with previous studies [8,10–12,23]. In the context of coronary atherosclerosis, a close relationship between platelets and the endothelium has been described: intact endothelium normally prevents platelet adhesion, whereas, in the presence of endothelial damage and activation, selectins mediate the first loose contact between circulating platelets and the vascular endothelium [24–26].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In particular, the more aggressive the procedures (i.e. with RA), the more pronounced this biomarker reduction, suggesting that endothelial dysfunction potentially occurs post‐PCI, in line with previous studies [8,10–12,23]. In the context of coronary atherosclerosis, a close relationship between platelets and the endothelium has been described: intact endothelium normally prevents platelet adhesion, whereas, in the presence of endothelial damage and activation, selectins mediate the first loose contact between circulating platelets and the vascular endothelium [24–26].…”
Section: Discussionsupporting
confidence: 74%
“…A coronary interventional procedure by itself is another important determinant of PR [7–13], which may significantly vary in the periprocedural setting. In particular, significant platelet activation has been associated with aggressive coronary interventions, such as rotational atherectomy (RA) [14].…”
Section: Introductionmentioning
confidence: 99%
“…In both RCA and SVG-RCA, neither TF-bearing MPs nor plasma TF were increased after stent implantation. This is in line with previous studies demonstrating no increase of intracoronary plasma TF level immediately after stent implantation in stable CAD [ 1 , 3 , 4 , 26 , 51 , 52 ] and in acute myocardial infarction [ 22 ]. However, there is a delayed increase of TF in coronary sinus blood 24 h after stent implantation [ 53 ], possibly secondary to immunological or inflammatory processes.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that arterial wall injury caused by PCI triggers transient hemostatic activation, leading to localized thrombosis and distal embolism. Strong and early activation of the hemostatic system occurs, which is possibly related to endothelial and atheromatous plaque disruption in response to balloon-induced arterial wall trauma [17,18]. Vascular endothelial damage during PCI leads to activation of platelet aggregation and subsequent distal embolism of microthrombi, and we considered that these distal embolisms are a major factor in the pathogenesis of PMI along with other lesion-related or procedural factors.…”
Section: Discussionmentioning
confidence: 99%